A new conodont biozone classification of the Ordovician System in South China - Wang, Zhi-Hao; Zhen, Yong Yi; Bergström, Stig M.; Wu, Rong-Chang; Zhang, Yuan-Dong; Ma, Xuan (Palaeoworld, 2019)
A revised conodont biozonal scheme for the Ordovician of South China is presented herein based on extensive studies following the pioneer work by the late Professor An and his co-workers in the 1980s. This new classification of 33 biozones and subbiozones includes the conodont succession of the Yangtze Platform (29 biozones and subbiozones), the Jiangnan Slope (17 biozones), and a unique succession in the Qinling Orogen (four Katian biozones). The proposed biozone scheme provides more accurate correlations of the Ordovician strata in South China. As the best known and most detailed Ordovician conodont biozone succession in eastern Gondwana and peri-Gondwana, it will serve as a standard reference for correlation not only in this region but also for comparisons with the well-established biozone successions in Baltoscandia and North America. Furthermore, this new scheme has the potential to improve the precision in reconstruction of the conodont biofacies architecture in space and time. It will also assist in advancing our understanding of the timing and magnitude of biodiversification, oceanographic, and geological events at both the local and global scale.